Pengaruh Pengetahuan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa - Albertus Maria Setyastanto; Endy Grade Tampubolon; Iramdan Iramdan (FOCUS, 2022)
This research is a follow-up study from previous research with the title "The Influence of Campus Environment on Student Learning Outcomes in Entrepreneurship Courses" is used as a basis for knowing the follow-up of the application of entrepreneurship courses into entrepreneurship practice. In preparing for entrepreneurial practice, students will have an interest in entrepreneurship. Interest in entrepreneurship is influenced by several factors. From these several factors, researchers are interested in entrepreneurial knowledge. With this interest, further studies will be carried out to sharpen knowledge. Therefore, this study aims to determine the effect of entrepreneurial knowledge on entrepreneurial interest. This research is a quantitative research with associative research type to determine the effect of entrepreneurial knowledge variable (X) on entrepreneurial interest (Y). The research was conducted for + 2 months at Unindra. The population and sample are Unindra students as many as 229 students as participants. Collecting data using an online questionnaire via google form which is tested for validity and reliability, then processed using linear regression testing and hypothesis testing. The results of the study indicate that there is a significant effect of entrepreneurial knowledge on entrepreneurial interest